Biological Actions, Implications, and Cautions of Statins Therapy in COVID-19 - Liu, Chengyu; Yan, Wanyao; Shi, Jiajian; Wang, Shun; Peng, Anlin; Chen, Yuchen; Huang, Kun (Frontiers in Nutrition, 2022)
The Coronavirus Disease 2019 (COVID-19) showed worse prognosis and higher mortality in individuals with obesity. Dyslipidemia is a major link between obesity and COVID-19 severity. Statins as the most common lipid regulating drugs have shown favorable effects in various pathophysiological states. Importantly, accumulating observational studies have suggested that statin use is associated with reduced risk of progressing to severe illness and in-hospital death in COVID-19 patients. Possible explanations underlie these protective impacts include their abilities of reducing cholesterol, suppressing viral entry and replication, anti-inflammation and immunomodulatory effects, as well as anti-thrombosis and anti-oxidative properties. Despite these benefits, statin therapies have side effects that should be considered, such as elevated creatinine kinase, liver enzyme and serum glucose levels, which are already elevated in severe COVID-19. Concerns are also raised whether statins interfere with the efficacy of COVID-19 vaccines. Randomized controlled trials are being conducted worldwide to confirm the values of statin use for COVID-19 treatment. Generally, the results suggest no necessity to discontinue statin use, and no evidence suggesting interference between statins and COVID-19 vaccines. However, concomitant administration of statins and COVID-19 antiviral drug Paxlovid may increase statin exposure and the risk of adverse effects, because most statins are metabolized mainly through CYP3A4 which is potently inhibited by ritonavir, a major component of Paxlovid. Therefore, more clinical/preclinical studies are still warranted to understand the benefits, harms and mechanisms of statin use in the context of COVID-19.